Human Resource Planning and Working Conditions as Psychological Predictors of Effective Service Delivery in Selected Public Hospitals in Ogun State, Nigeria - Olanipekun, Lateef Okikiola; Taiwo, Tejumoluwa Emmanuel (Zien Journals, 2021)
The problematic situation of developing societies to retain their medical personnel given their inability to institute viable manpower plan and conducive work environment that should be suitable for the fulfillment of the lofty aspirations of medical personnel is what necessitates the study. Hence, the study investigated the relationship between human resource planning, working conditions and service delivery in Ogun State public Hospitals. Data were obtained from employees of ten (10) purposively selected public Hospitals in Ogun State using the convenience sampling technique; through a structured questionnaire which was administered to medical and non-medical personnel of randomly selected public hospitals in five zones in Ogun State. The study adopted a descriptive design in which quantitative (questionnaire) method was utilised for data collection. Multistage sampling techniques were employed in selecting respondents for the study. A total of 295 employees were utilised in gathering the quantitative data. Descriptive statistics (frequency count and percentage distribution) were deployed in analysing the data; correlation and regression analysis were employed in testing the three stated hypotheses. The finding of this study revealed that in the ten selected hospitals from the five zones in Ogun State, there was a positive relationship between human resource planning and service delivery, it was also revealed that human resource planning and working conditions have significant effect on service delivery. The study concluded that Human resource planning and working conditions are of utmost importance to the actualisation of organisational objectives as well as customers’ satisfaction in terms of service delivery; thus, it was recommended that managements of Ogun State public Hospitals should embark on radical reorganisation of its objectives and aims which must primarily cater for the welfare of its personnel as this is fundamental to service delivery and will therefore redirect the mindset of the public from viewing public hospitals as death traps and begin to see them as a reliable solution haven to all form of health challenges.
Keywords: Human Resource Planning; Working Conditions; Service Delivery; Public Hospitals